Balanced Scorecard-Based Approach to Ascertain the Quality of Education - Sangka, Kreshna; Hussain, Omar (IEEE Computer Society, 2010)
Educational Providers should continually monitor and measure their performance in terms of delivering quality education to the students. Although the importance of such an assessment process has been stressed in the literature, no framework has been proposed that considers all the different relevant factors and determines semantically the level of the quality of education being delivered. In order to provide such an approach, in this paper we propose a framework by which the quality of education being delivered in a subject in an Indonesian university can be determined by using the Balanced Scorecard (BSC). The proposed approach will capture the different factors to be considered from the different perspectives and assimilate them to determine the quality of education. The resultant analysis will provide important inputs to the different stakeholders involved in taking appropriate measures to ensure that students' learning experiences can be maintained at a certain desired level.